Secondary School Instructional Response to the World of Work: Employers’ Needs and Pedagogical Practices - ABDI , LEMESSA; KENEA, AMBISSA (Journal of Interdisciplinary Studies in Education, 2023)
This study examines the relevance of secondary school pedagogical responses to the skills demand of the world of work. Employers of secondary school graduates, secondary school principals, teachers and students in Oromia, Ethiopia, were the target population of the study. Results revealed that school leaders and teachers perceived preparation for national examination and higher education as the major intent of secondary education. They had no adequate understanding of the role of secondary education in preparing students for the world of work. The study identified that communication skills, teamwork, time management, independent work, ability and readiness to learn, and self-management are the competencies employers require from employees who graduated from secondary school. However, a teacher-centered instructional approach that has an insignificant contribution to acquiring the required work skills was the dominant pedagogical strategy employed in the schools. Thus, it is concluded that the space provided to prepare students for work in secondary school instruction was not relevant enough to equip students with the competencies required in the world of work.